Composition Structure And Distribution Patterns Of Pandanaceae Family Plants In Batang Gadis Resort 7 Sopotinjak National Park, Mandailing Natal District North Sumatra - Sofi Caesar Triani; Melfa Aisyah Hutasuhut; Zahratul Idami (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2023)
The Pandanaceae family includes Monocotyledoneae plants that have tree, liana, and shrub habitus. This study aims to determine the types of the Pandanaceae family, diversity index, and distribution patterns of the Pandanaceae family at Resort 7 Sopotinjak Batang Gadis National Park, Batang Natal District, Mandailing Natal Regency, North Sumatra which was carried out in February - April 2022. The method used in this research is a survey method with the technique of making quadrat plots by purposive sampling on 3 research transects, each transect consisting of 8 plots. The results obtained 7 species from the Pandanaceae family, namely Benstonea eatrocarpa (Griff.), Benstonea parva (Ridl.) Callm & Buerki, Benstonea sp., Freycinetia angustifolia Blume, Freycinetia sumatrana Hemsl, Pandanus furcatus Roxb., Pandanus houlettii Carriere. The diversity index of the Pandanacaeae family in Resort 7 Sopotinjak Batang Gadis National Park in transect 1 was 0.397, in transect 2 was 0.637, and in transect 3 was 0.079 which indicated that the level of diversity was low. The morisita index (Id) of the Pandanaceae family in Resort 7 Sopotinjak Batang Gadis National Park is 9.45, which indicates that the distribution pattern is clustered. The Pandanaceae family is found in highland tropical forests with high rainfall and reproduces vegetatively (budding) under favorable environmental conditions.